Sepsis: Inflammation Is a Necessary Evil - Nedeva, Christina; Menassa, Joseph; Puthalakath, Hamsa (Frontiers in Cell and Developmental Biology, 2019)
Sepsis is one of the leading causes of deaths world-wide and yet there are no therapies available other than ICU treatment. The patient outcome is defined by a complex interplay between the pro and anti-inflammatory responses of the body i.e. a homeostatic balance between these two competing events to be achieved for the patient’s recovery. The initial attempts on drug development mainly focused on controlling inflammation, however without any tangible outcome. This was despite most deaths occurring during the subsequent immune paralysis. Recently, the focus has shifted to understanding immune paralysis (caused by apoptosis) to develop therapeutic drugs. However, in this review we put forth an argument for a proper understanding of the molecular basis of inflammation as well as apoptosis for developing an effective therapy.